Neural blastocyst complementation enables mouse forebrain organogenesis. (1st November 2018) - Chang, Amelia; Liang, Zhuoyi; Dai, Hai-Qiang; Chapdelaine-Williams, Aimee; Andrews, Nick; Bronson, Roderick; Schwer, Bjoern; Alt, Frederick
Abstract Genetically modified mice are commonly generated by the microinjection of pluripotent embryonic stem (ES) cells into wild-type host blastocysts1, producing chimeric progeny that require breeding for germline transmission and homozygosity of modified alleles. As an alternative approach and to facilitate studies of the immune system, we previously developed RAG2-deficient blastocyst complementation2 . Because RAG2-deficient mice cannot undergo V(D)J recombination, they do not develop B or T lineage cells beyond the progenitor stage2 : injecting RAG2-sufficient donor ES cells into RAG2-deficient blastocysts generates somatic chimaeras in which all mature lymphocytes derive from donor ES cells. This enables analysis, in mature lymphocytes, of the functions of genes that are required more generally for mouse development3 . Blastocyst complementation has been extended to pancreas organogenesis4, and used to generate several other tissues or organs5–10, but an equivalent approach for brain organogenesis has not yet been achieved. Here we describe neural blastocyst complementation (NBC), which can be used to study the development and function of specific forebrain regions. NBC involves targeted ablation, mediated by diphtheria toxin subunit A, of host-derived dorsal telencephalic progenitors during development. This ablation creates a vacant forebrain niche in host embryos that results in agenesis of the cerebral cortex and hippocampus. Injection of donor ES cells into blastocysts with forebrain-specific targeting of diphtheria toxin subunit A enables donor-derived dorsal telencephalic progenitors to populate the vacant niche in the host embryos, giving rise to neocortices and hippocampi that are morphologically and neurologically normal with respect to learning and memory formation. Moreover, doublecortin-deficient ES cells—generated via a CRISPR–Cas9 approach—produced NBC chimaeras that faithfully recapitulated the phenotype of conventional, germline doublecortin-deficient mice. We conclude that NBC is a rapid and efficient approach to generate complex mouse models for studying forebrain functions; this approach could more broadly facilitate organogenesis based on blastocyst complementation. Neural blastocyst complementation creates a vacant forebrain niche in host embryos that can be populated by donor embryonic stem cell-derived dorsal telencephalic progenitors, resulting in a mouse brain organogenesis model.